Men's experience with penile rehabilitation following radical prostatectomy: a qualitative study with the goal of informing a therapeutic intervention. Issue 12 (24th February 2015) - Nelson, Christian J.; Lacey, Stephanie; Kenowitz, Joslyn; Pessin, Hayley; Shuk, Elyse; Roth, Andrew J.; Mulhall, John P.
Abstract: Background: Erectile rehabilitation (ER) following radical prostatectomy (RP) is considered an essential component to help men regain erectile functioning; however, many men have difficulty adhering to this type of program. This qualitative study explored men's experience with ER, erectile dysfunction (ED), and ED treatments to inform a psychological intervention designed to help men adhere to ER post‐RP. Methods: Thirty men, 1‐to‐3‐years post‐RP, who took part in an ER program, participated in one of four focus groups. Thematic analysis was used to identify the primary themes. Results: Average age was 59 years (standard deviation = 7); mean time since surgery was 26 months (standard deviation = 6). Six primary themes emerged: (1) frustration with the lack of information about postsurgery ED; (2) negative emotional impact of ED and avoidance of sexual situations; (3) negative emotional experience with penile injections and barriers leading to avoidance; (4) the benefit of focusing on the long‐term advantage of ER versus short‐term anxiety; (5) using humor to help cope; and (6) the benefit of support from partners and peers. Conclusions: Men's frustration surrounding ED can lead to avoidance of sexual situations and ED treatments, which negatively impact men's adherence to an ER program. The theoretical construct of acceptance and commitment therapy was used to place the themes into a framework to conceptualize the mechanisms underlying both avoidance and adherence in this population. As such, acceptance and commitment therapy has the potential to serve as a conceptual underpinning of a psychological intervention to help men reduce avoidance to penile injections and adhere to an ER program. Copyright © 2015 John Wiley & Sons, Ltd.